EFFECT OF DIFFERENT ENERGY LEVELS ON GROWTH, CARCASS TRAITS , BODY COMPOSITION AND DIGESTIBILITY OF NUTRIENT IN AWASSI LAMBS - Yateem, CH. A. M.; Alkass, J. E.; Mustafa, K. N. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This experiment was designed to investigate the effect of different level of energy on growth, carcass traits, body composition, digestibility and some blood parameters. Twenty one Awassi lambs (4 month old and 23 kg body weight) were used and after 10 days of adaptation, the lambs were divided equally and randomly and penned individually into three treatment groups, and fed ad lib on low (10.8 T1) medium (11.6 T2) and high (12.3 T3 MJ/kg DM). After 72 days of fattening, 5 lambs from each treatment were chosen and slaughtered. Results revealed that lambs of T3 had numerically higher daily gain (189.72 g), lower dry matter intake (849.46 g), higher feed efficiency (4.7), higher dressing percentage (48.43) and a significant increase (P≤0.05) was noticed in dry matter, organic matter, crude protein, nitrogen free extract and total digestible nutrient as compared with lambs received low or medium level of energy. It could be concluded that the high dietary energy produce the best performance, nutrient digestion and carcass trait of lambs.